LANDASAN FILSAFAT ILMU DALAM ADMINISTRASI PENDIDIKAN DASAR: IMPLIKASI TERHADAP PENINGKATAN PROFESIONALISME TENAGA KEPENDIDIKAN DI SEKOLAH DASAR ERA TRANSFORMASI DIGITAL - Rizki, Ridonal; Salsabila, Irsa; Jasrial; Nellitawati; Ayu Ningrum, Tia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of primary education (Sekolah Dasar/SD) is substantially determined by the professionalism of educational staff, which includes school principals, administrative staff, laboratory technicians, and librarians at the elementary school level. However, national data from the Ministry of Education, Culture, Research, and Technology (2022) reveals that only 61.3% of primary school principals in Indonesia meet the minimum competency standards, indicating a critical gap in educational staff professionalism. This study argues that one root cause of this gap is the absence of a solid philosophical foundation in the training and professional development of educational staff. This study aims to: (1) examine the ontological, epistemological, and axiological foundations of educational administration at the primary school level; (2) analyze the contribution of the philosophy of science to the professionalism of primary school educational staff in the digital transformation era; (3) identify challenges in implementing philosophy-based professional development; and (4) propose the Philosophical Triadic Model (PTM/MTF) as a conceptual framework for developing the professionalism of primary school educational staff. This research employs a qualitative library research design. Data were systematically collected from grand theory primary sources and secondary sources comprising SINTA 1-2 nationally indexed and Scopus/WoS internationally indexed journal articles (2019-2024). Content analysis followed Miles, Huberman and Saldana (2014). Findings indicate that ontological, epistemological, and axiological foundations are significantly underdeveloped in current primary school administration practice. The proposed PTM offers three integrated pillars: ontological strengthening through professional identity formation, epistemological strengthening through evidence-based practice, and axiological strengthening through ethical leadership culture. The PTM is distinguished from existing frameworks by its explicit integration of digital transformation challenges specific to the primary education context. Implications for policy reform of principal and administrative staff training programs are discussed.